The effect of using the interactive video accompanying the static training in learning some basic skills of a model school in squash - Shukr, Ali Hassan; Obaid, Ali Jalal; Qadouri , YasserWajih (International Journal of Psychosocial Rehabilitation, 2020)
Lately great interests have emerged to find educational alternatives to teach and improve motor skills according to modern educational methods that take into account individual differences and speed in learning for the learner through individual learning that the learner adopts by teaching himself by passing through various educational situations to acquire skills and information in the way he is The learner is the focus of the educational process and among these alternatives the interactive video, the researchers noted through the educational training units at the Model Squash School of the Central Union, and that most of the methods and methods used in learning basic skills take a lot of time in the educational program and do not involve the learner in the actual performance and depend entirely According to the performance techniques provided by the coach and that these methods do not take into account individual differences in mental abilities and skills and the extent of their reception of information in addition to the ages of these players that require the use of means of suspense in the process of teaching them to the ideal performance, from here came the research problem and try to find solutions through knowledge The effect of using interactive video accompanying lactation I am hard at learning some basic skills of a typical squash school. The most important goals are to identify the effect of using the interactive video accompanying the static training in learning some basic skills of the model school in squash. The experimental method was used for its suitability and the nature of the research. The researchers chose the research sample in the deliberate manner in the manner of the experimental and control groups. The research community included a number of Squash Academy players for beginners with ages (13-15) years of (22) novice players and excluded players who are not committed to training and thus became the final research sample And their number (16) players and they sincerely represent the research community at a rate of (100%). They were divided into two groups in a random manner by (8) players for the experimental group and (8) players for the control group who were conducted the main experiment, the most important conclusions: The results proved that the style The interactive video accompanying the static training is suitable for learning some basic skills in squash, and this is what the results showed. The method of implementing the educational units used gave positive results in facilitating the process of learning the skills of front and back kick and transmission from both sides of the squash court.